Simplex method for slender column design - Ong, Keene Wei Xiang (2017)
Columns have always been one of the key structural elements in a building, having the role of transferring lateral and vertical load to the foundation. To maximize the aesthetical appeal as well as the floor area in a building, slender columns have made its way to various modernized buildings. Having said that, this final year project is focused on the study of reinforced slender columns that were subject to short term axial loading and uniaxial bending of the pinned-pinned column. Eccentricity was also applied to create end moment in the column when it is axially loaded. The objective of this report is to evaluate different column design methods and to present findings and recommendations for the slender column analysis. Focusing on the Eurocode 2 moment magnification, the comparisons are made between the Eurocode 2 additional moment method as well as the ACI 318 moment magnification method. Elaborate and thorough analysis across 150 column data have been made with respect to column parameters, such as eccentricity to depth ratio (e/h), length to depth ratio (L/h), area of steel reinforcement ratio(As/bh) and concrete strength. (fcu) Indicative results have shown the following relationship between column parameters and design axial capacity. When e/h and L/h increases, axial capacity decreases. As area of steel reinforcement ratio and concrete strength increases, the axial capacity increases. In accordance to the analysis with all 150 columns, the factor of safety for EC2 moment magnification method ranks itself in the middle, with EC2 additional moment method being the least conservative and the ACI 318 moment magnification method being the most conservative. With reference to Column HJ, closer look at the e/h and L/h analysis based on that column series suggests that as the effective length increases, the EC2 moment magnification method’s axial load capacity decreases accordingly, representing the raise in the factor of safety. From the analysis for steel reinforcement ratio, the mentioned method reflects that steel reinforcement of 3.25% and above will cause a substantial decrease in the factor of safety. Increment in concrete strength does shows that the axial load capacity increases, much like the other methods. Hence, the takeaway is that the method can be utilized for column design, but the method should be considered for a reduction in the factor of safety when column of e/h ratio is more than 0.25 and L/h ratio is more than 15, as it is over conservative. Further studies on the EC2 moment magnification method should be conducted on columns with high strength concrete, since design methodology between the factored and unfactored results are very identical.